Economic relations with regions neighbouring the euro area in the "Euro Time Zone" - Francesco Mazzaferro; Arnaud Mehl; Michael Sturm; Christian Thimann; Adalbert Winkler (European Central Bank (ECB), 2002)
This paper reviews the economic, monetary and financial relations between the EU and the euro area and a set of countries in a broad set of neighbouring regions. The 80 or so countries are mostly classified as transition, emerging or developing economies and belong to four main regions: the Western Balkans; the European part of the Commonwealth of Independent States; the Middle East and Northern Africa; and Sub-Saharan Africa. In many respects, these countries are diverse; however, some common features can also be identified. One of these common features is the fact that the euro area is their largest trading partner and the largest originator of international bank credit, foreign direct investment and official development assistance; meanwhile, from a euro area perspective, while these countries account for a somewhat smaller share of external trade, they are important as providers of energy, other raw materials and agricultural products.
Keywords: 330; Euro; Internationale Wirtschaftsbeziehungen; Internationaler Finanzmarkt; Wechselkurs; EU-Staaten; Osteuropa; GUS-Staaten; Westasien; Nordafrika; Zentralafrika